COLLEGIAL LEADERSHIP: AN EDUCATIONAL LEADERSHIP FOR STUDENTS WITH SPECIAL NEEDS IN MUHAMMADIYAH SCHOOLS - Supriyanto, Supriyanto; Rokhman, Januar Nur; Puspitasari, Fantika Febry (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This research aims to describe the form of collegial leadership as an effort to optimize education for students with special needs in Muhammadiyah schools. Furthermore, this study employs an ethnographic approach. The research locus is SMP Muhammadiyah 2 Malang. Data were collected through observation and unstructured interviews with key informants. After data collection, it was analyzed using the Miles and Huberman analysis model. The results of the research indicate that SMP Muhammadiyah 2 Malang implements several programs related to the education of Children with Special Needs (CSN) that align with the principles of collegial leadership. These include making regular students shadow teachers, involving all teachers and school staff, and engaging CSN parents in various activities. However, the education of disabled individuals in the school faces challenges in several aspects, such as continuous curriculum development, negative societal perceptions, and financing.